Endocytosis in Plasmodium and Toxoplasma Parasites. Issue 6 (June 2020) - Spielmann, Tobias; Gras, Simon; Sabitzki, Ricarda; Meissner, Markus
Abstract : Endocytosis is critical for many functions in eukaryotic cells. Uptake of host cell cytosol, an indispensable endocytic process in malaria blood-stage parasites, has been known for a long time. However, it is only recently that the proteins involved in this process have started to emerge. Unexpectedly, some of these proteins revealed a critical role for endocytosis in artemisinin resistance. More recently, endocytosis was discovered in both intracellular and extracellular Toxoplasma gondii parasites. Here, we review these findings, compare the endolysosomal systems of Toxoplasma and Plasmodium parasites, and present current knowledge about endocytic mechanisms in apicomplexans. Highlights: Endocytosis plays critical roles in Plasmodium and Toxoplasma parasites. Host cell cytosol uptake is a prominent endocytic process in malaria blood-stage parasites. Endocytosis in both intra- and extracellular T. gondii was recently revealed as an important process. The endolysosomal system in these parasites shows conserved and noncanonical features. Future studies should consider the interconnectedness of endocytic and secretory functions.